2017
DOI: 10.1093/treephys/tpx055
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and small interference RNAs participate in the regulation of MADS-box genes involved in dormancy in sweet cherry (Prunus avium L.)

Abstract: Epigenetic modifications can yield information about connections between genotype, phenotype variation and environmental conditions. Bud dormancy release in temperate perennial fruit trees depends on internal and environmental signals such as cold accumulation and photoperiod. Previous investigations have noted the participation of epigenetic mechanisms in the control of this physiological process. We examined whether epigenetic modifications were modulated in MADS-box genes, potential candidates for the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 55 publications
4
59
0
Order By: Relevance
“…In effect, global and specific levels of genomic DNA cytosine methylation change during bud development in chestnut ( Santamaría et al, 2009 ) and apple ( Kumar et al, 2016 ), and recent functional studies reveal the important role of DNA methylation enzymes in seasonal dormancy regulation: overexpression of a chestnut DEMETER-like ( CsDML ) DNA demethylase accelerates photoperiodic-dependent bud formation ( Conde et al, 2017b ), whereas down-regulation of poplar DEMETER-like ( PtaDML10 ) delays bud break ( Conde et al, 2017a ) in poplar. In sweet cherry ( Prunus avium ), specific DNA methylations and siRNAs are associated with silencing of the DAM -like gene PavMADS1 during dormancy release ( Rothkegel et al, 2017 ). Modification of transcript stability by microRNA action has been also hypothesized to participate in bud dormancy regulation.…”
Section: Growth Resumption and Floweringmentioning
confidence: 99%
“…In effect, global and specific levels of genomic DNA cytosine methylation change during bud development in chestnut ( Santamaría et al, 2009 ) and apple ( Kumar et al, 2016 ), and recent functional studies reveal the important role of DNA methylation enzymes in seasonal dormancy regulation: overexpression of a chestnut DEMETER-like ( CsDML ) DNA demethylase accelerates photoperiodic-dependent bud formation ( Conde et al, 2017b ), whereas down-regulation of poplar DEMETER-like ( PtaDML10 ) delays bud break ( Conde et al, 2017a ) in poplar. In sweet cherry ( Prunus avium ), specific DNA methylations and siRNAs are associated with silencing of the DAM -like gene PavMADS1 during dormancy release ( Rothkegel et al, 2017 ). Modification of transcript stability by microRNA action has been also hypothesized to participate in bud dormancy regulation.…”
Section: Growth Resumption and Floweringmentioning
confidence: 99%
“…Several studies have been focused on a group of genes, called DORMANCY-ASSOCIATED MADS-BOX (DAM) and other orthologs of SHORT VEGETATIVE PHASE (SVP) genes, which recently have emerged as potential regulators of dormancy in several species such as almond (Prunus dulcis; Prudencio et al, 2018), apple (Malus x domestica; Falavigna et al, 2014;Wu et al, 2017), apricot (Prunus armeniaca; Balogh et al, 2019), Chinese cherry (Prunus pseudocerasus; Zhu et al, 2015), hybrid aspen (Populus tremula x tremuloides; Singh et al, 2018), Japanese apricot (Prunus mume; Sasaki et al, 2011), kiwifruit (Actinidia chinensis; Wu et al, 2019;Actinidia deliciosa;Wu et al, 2012), leafy spurge (Euphorbia esula; Horvath et al, 2008), pear (Pyrus pyrifolia; Saito et al, 2015), and sweet cherry (Prunus avium; Rothkegel et al, 2017). These genes were firstly identified in an evergrowing mutant (evg) of peach (Prunus persica) that shows a non-dormant phenotype, maintaining apical growth and persistent leaves in response to dormancy inducing conditions (Bielenberg et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In Mei (Prunus mume), all PmDAM genes (PmDAM1-PmDAM6) were strongly repressed during prolonged cold exposure in winter and maintained at low levels till the release of endodormancy, and overexpression of PmDAM6 in poplar (Populus tremula × Populus tremuloides) led to growth cessation and terminal bud set and bud endodormancy, even under favorable conditions (Sasaki et al, 2011). Interestingly, similar to the functional profiles of FLC genes and their homologs in Brassicaceae, some of the DAM genes, such as DAM5 and DAM6 in peach, could be suppressed by chilling temperatures and are inversely correlated with bud break rate (Jimenez et al, 2010), and those processes are also regulated by histone modifications and DNA methylation (de la Fuente, Conesa, Lloret, Badenes, & Rios, 2015;Leida et al, 2012;Rothkegel et al, 2017;Saito et al, 2015), as well as day length (Li, Reighard, Abbott, & Bielenberg, 2009) and plant hormones (Falavigna et al, 2019;Kurokura et al, 2013;Rinne et al, 2011;Tuan et al, 2017;Tylewicz et al, 2018), similar to FLC in Brassicaceae (Rios, Leida, Conejero, & Badenes, 2014). These results suggested that the biological functions of SVP genes, rather than FLC genes, might have been evolutionarily enhanced for bud dormancy in Rosaceae (Falavigna et al, 2019. Bud dormancy is an adaptive process that allows perennial plants to survive the winter conditions of temperate climates (Falavigna et al, 2019;Paul, Rinne, & van der Schoot, 2014).…”
Section: Introductionmentioning
confidence: 99%